Quality of Beverage Intake and Cardiometabolic and Kidney Outcomes: Insights From the STANISLAS Cohort - Wagner, Sandra; Merkling, Thomas; Girerd, Nicolas; Bozec, Erwan; Van den Berghe, Laurie; Hoge, Axelle; Guillaume, Michèle; Kanbay, Mehmet; Cakir-Kiefer, Céline; Thornton, Simon N.; Boivin, Jean-Marc; Mercklé, Ludovic; et al. (Frontiers in Nutrition, 2022)
Beverages are an important aspect of the diet, and their quality can possibly affect health. The Healthy Beverage Index (HBI) has been developed to take into account these effects. This study aimed to highlight the relationships between health and beverage quality by assessing the association of the HBI and its components with kidney and cardiometabolic (CM) outcomes in an initially healthy population-based familial cohort. This study included 1271 participants from the STANISLAS cohort. The HBI, which includes 10 components of habitual beverage consumption, was calculated. Associations of the HBI and its components with estimated glomerular filtration rate (eGFR), albuminuria, hypertriglyceridemic waist (HTG waist), metabolic syndrome (MetS), carotid-femoral pulse wave velocity (cfPWV), carotid intima-media thickness (cIMT) and left ventricular mass (LV mass) were analyzed using multivariable linear or logistic regression models. The median HBI score was 89.7 (78.6-95) out of 100 points. While the overall HBI score was not significantly associated with any of the studied outcomes, individual HBI components, were found differently associated with the outcomes. cfPWV and cIMT were lower in participants who did not meet the full-fat milk criteria (p=0.03 and 0.001, respectively). In men, higher cfPWV was observed for the ‘Low Fat milk’ (p=0.06) and ‘Alcohol’ (p=0.03) non-adherence criteria. Odds of HTG waist were higher with the non-adherence to sugar-sweetened beverages criteria (p<0.001). eGFR was marginally higher with non-adherence to the coffee/tea criteria (p=0.047). In this initially healthy population, HBI components were differently associated with kidney and cardiometabolic outcomes, despite a good overall HBI score. Our results highlight specific impacts of different beverage types and suggest that beverages could have an impact on kidney and cardiometabolic health.